An Interdisciplinary Approach to Upright Partially Impacted Maxillary Second Molar- A Case Report - Narula, Khyati (Orthodontic Journal of Nepal, 2024)
We present a case of a partially impacted maxillary right second molar treated by ortho-surgical approach. The patient had a Class II malocclusion and was treated using sectional orthodontic mechanics after surgical uprighting of tooth 17. The treatment was finished in 8 months with adequate uprighting of the maxillary second molar and the results were stable after 1 year. When other conventional treatment modalities are ineffective or contraindicated the surgical uprighting approach can be used.